A Case Study: House Condition of Stunting Children at Tidung Island, Jakarta, Indonesia - Nainggolan, Susanti Muvana; Siahaan, Uras; Saputra, Stepanus Andi; Langi, Louisa Ariantje; Wirawan, Luky; Vito, Juan (RUSTIC, 2025)
A house or dwelling is one of the essential architectural elements designed to meet human needs. A house serves as a shelter, a place for protection, rest, and various activities. Houses and dwellings are designed to support their occupants by providing essential needs, security, aesthetics, a sense of pride, and even contributing to the occupants' health. Housing is an element that is often challenging to access and address in detail, including residential homes on Tidung Island. The varying sizes of houses and their increasing proximity to one another due to limited land availability have resulted in many homes losing access to natural lighting and ventilation. Previous research has indicated that the living environment significantly influences the prevalence of stunting in children. Stunting is a condition of malnutrition in children under the age of five that often affects their health and growth. The Jakarta city government of Indonesia already tries to reduce stunting rates among children by ensuring adequate nutrition. However, in some areas, progress has been slower, including on Tidung Island. According to previous studies, the factors contributing to stunting in children is not only to nutritional deficiencies, environmental conditions, housing quality, and poor sanitation also play a significant role in increasing the number of stunted children. As an initial study phase, this research aims to observe the living conditions of children experiencing stunting.